An Immunocompetent Adult Male Presented with a Liver Abscess Caused by the Mycobacterium tuberculosis: A Case Report from India - Akash Pawar; Sagar Khadanga; Abhishek Singhai (Case Reports in Infectious Diseases)
A liver abscess is a collection of purulent fluid in the liver parenchyma caused by a variety of etiological organisms such as bacteria, protozoa, and in rare occasions fungi. Mycobacterium tuberculosis (MTB) is a frequent and widespread infection in underdeveloped nations such as India, which can manifest in many ways. Tuberculosis mostly affects the lungs, although it can also affect any organ in the body. We are reporting a case of liver abscess caused by MTB infection in order to raise general awareness among physicians about the importance of suspecting and ruling out tuberculosis as a cause of liver abscess. To the best of our knowledge, there have been very few such cases reported from India/the rest of the world.